2020
DOI: 10.1111/aogs.13936
|View full text |Cite
|
Sign up to set email alerts
|

Maternal arterial blood gas values during delivery: Effect of mode of delivery, maternal characteristics, obstetric interventions and correlation to fetal umbilical cord blood

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
7
0
4
Order By: Relevance
“…Fard et al found a positive correlation between FEV1 and PaO2 in patients with chronic bronchitis, and a negative significant correlation with PaCO2 [ 22 ] . Zaigham et al found that maternal arterial pH, pCO 2 , and lactate values were signifi cantly correlated with the values in UCB [ 7 ] . In the present study, a signifi cant correlation was determined between maternal FEV1, FVC, and umbilical cord pH and base excess values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fard et al found a positive correlation between FEV1 and PaO2 in patients with chronic bronchitis, and a negative significant correlation with PaCO2 [ 22 ] . Zaigham et al found that maternal arterial pH, pCO 2 , and lactate values were signifi cantly correlated with the values in UCB [ 7 ] . In the present study, a signifi cant correlation was determined between maternal FEV1, FVC, and umbilical cord pH and base excess values.…”
Section: Discussionmentioning
confidence: 99%
“…Acid-base balance in fetal blood may vary depending on the type of delivery, i. e., cesarean or vaginal delivery, or the type of anesthesia used in cesarean section [19]. Similarly, it was shown that maternal blood gas also changes according to the mode of delivery, epidural anesthesia, and administration of oxytocin [7]. The effort spent after uterine contractions with vaginal delivery results in impaired oxygenation, anaerobic glycolysis, and lactate accumulation in both mother and fetus, and while the increase in maternal arterial blood base deficit indicates metabolic acidemia, pCO 2 decreases with compensation-oriented hyperventilation [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies ( 41 43 ) also show a strong association between instrumented delivery and fetal acidosis: There is a large volume of scientific literature that maintains that instrumented vaginal birth increases the incidence of fetal compromise compared with eutocic vaginal birth ( 44 47 ), a conclusion which bears similarity to our results. Kapaya et al ( 46 ) compared the different types of delivery, finding that instrumented birth corresponded to the highest percentage of neonates with pathological pH values (45%) and elective cesarean the lowest (0.3), and Zaigham et al ( 48 ), found a significantly lower pH, pCO 2 , pO 2 , and sO 2 in mothers delivering vaginally in comparison with planned cesarean sections. The significant differences in acid–base values according to mode of delivery is based on processes such as during vaginal delivery, the sheer force of uterine contractions and bearing down results in impaired oxygenation and anaerobic glycolysis with lactate accumulation in both the mother and fetus ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kapaya et al ( 46 ) compared the different types of delivery, finding that instrumented birth corresponded to the highest percentage of neonates with pathological pH values (45%) and elective cesarean the lowest (0.3), and Zaigham et al ( 48 ), found a significantly lower pH, pCO 2 , pO 2 , and sO 2 in mothers delivering vaginally in comparison with planned cesarean sections. The significant differences in acid–base values according to mode of delivery is based on processes such as during vaginal delivery, the sheer force of uterine contractions and bearing down results in impaired oxygenation and anaerobic glycolysis with lactate accumulation in both the mother and fetus ( 48 ).…”
Section: Discussionmentioning
confidence: 99%